KONFLIK KEPENTINGAN DALAM PENEGASAN BATAS DAERAH (STUDI KASUS BATAS DAERAH KABUPATEN PELALAWAN DAN KABUPATEN INDRAGIRI HULU) TAHUN 2016-2021 - Anisa Permata Rahma; Tito Handoko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The conflict over the boundaries of an area in Riau Province is a dispute between Pelalawan Regency and Indragiri Hulu Regency. Conflict Border disputes occur due to several factors ranging from unclear boundary determination from the law on the formation of new autonomous regions, competition for natural resources, politics, to government services. The theory used in this research is the theory of Ralf Dahrendorf. This study aims to find out the role of the Pelalawan Regency and Indragiri Hulu Regency governments in resolving regional boundary conflicts between Ukui II Village, Pelalawan Regency and Redang Seko Village, Indragiri Hulu Regency. This study uses the Regulation of the Minister of Home Affairs of the Republic of Indonesia No. 45 of 2016 concerning Guidelines for Determining and Confirming Village Boundaries and what is the role of government in dealing with the problem of regional boundaries between Pelalawan Regency and Indragiri Hulu Regency in Ukui II Village and Redang Seko Village. The data used by researchers used data collection techniques by way of interviews, documentation and literature review. The research indicator is that there have been several meetings to discuss this issue which were facilitated by the Government of Indragiri Hulu Regency and Pelalawan Regency. The causal factors have many dimensions and are interrelated with one another. These factors include: structural factors, interest factors, human relations and data conflicts, all of which can be categorized as background factors, conflict triggers. Settlement of the border conflict between Indragiri Hulu Regency and Pelalawan Regency was carried out through mediation by the Governor and conflict resolution was carried out outside the court. The problems with the boundaries of the two areas say different things. Until now, the Pelalawan Regency said that this problem had been resolved with the issuance of a decree in 2021, but the Indragiri Hulu Regency did not know about this. Keywords: Conflict of Interest, Regional Boundary, Village